Material security, life history, and moralistic religions: A cross-cultural examination - Purzycki, Benjamin Grant (PLoS One, 2018)
Researchers have recently proposed that “moralistic” religions—those with moral doctrines, moralistic supernatural punishment, and lower emphasis on ritual—emerged as an effect of greater wealth and material security. One interpretation appeals to life history theory, predicting that individuals with “slow life history” strategies will be more attracted to moralistic traditions as a means to judge those with “fast life history” strategies. As we had reservations about the validity of this application of life history theory, we tested these predictions with a data set consisting of 592 individuals from eight diverse societies. Our sample includes individuals from a wide range of traditions, including world religions such as Buddhism, Hinduism and Christianity, but also local traditions rooted in beliefs in animism, ancestor worship, and worship of spirits associated with nature. We first test for the presence of associations between material security, years of formal education, and reproductive success. Consistent with popular life history predictions, we find evidence that material security and education are associated with reduced reproduction. Building on this, we then test whether or not these demographic factors predict the moral concern, punitiveness, attributed knowledge-breadth, and frequency of ritual devotions towards two deities in each society. Here, we find no reliable evidence of a relationship between number of children, material security, or formal education and the individual-level religious beliefs and behaviors. We conclude with a discussion of why life-history theory is an inadequate interpretation for the emergence of factors typifying the moralistic traditions.